Growth hormone and connective tissue in exercise - Doessing, S.; Kjaer, M. (Scandinavian Journal of Medicine & Science in Sports, 2005)
Over the last few years, growth hormone (GH) has become increasingly popular as doping within different sports. However, the precise mechanisms behind the ergogenic (performance enhancing) effects of GH in athletes are still being debated. Besides a well-documented stimulatory effect of GH on carbohydrate and fatty acid metabolism, and a possible anabolic effect on myofibrillar muscle protein, we suggest a role for GH as an anabolic agent in connective tissue in human skeletal muscle and tendon. Given the importance of the connective tissue for the function of skeletal muscle and tendon, a strengthening effect of GH on connective tissue could fit with the ergogenic effect of GH experienced by athletes.